Consumer Knowledge and Acceptance of “Algae” as a Protein Alternative: A UK-Based Qualitative Study - Rochelle Embling (Foods, 2022)
Overconsumption of meat has been recognised as a key contributing factor to the climate emergency. Algae (including macroalgae and microalgae) are a nutritious and sustainable food source that may be utilised as an alternative to animal-based proteins. However, little is known about the consumer awareness and acceptance of algae as a protein alternative. The aim of this qualitative study was to develop a rich and contextualised understanding of consumer beliefs about the use of algae in novel and innovative food products. A total of 34 participants from the UK assisted with our study. Each participant engaged in one focus group, with six focus groups conducted in total. Existing consumer knowledge of algae was discussed before participants explored the idea of algae-based food products. Reflexive (inductive) thematic analysis was used to analyse these data. Results showed that consumers have limited pre-existing knowledge of algae as a food source; however, participants were open to the idea of trying to consume algae. This anticipated acceptance of algae was influenced by several product attributes, including perceived novelty, edibility, healthiness, sustainability, and affordability. These findings highlight algae as a promising protein alternative to support plant-forward diets in the UK and identify key attributes to consider in future product development and marketing strategies.